FORMATION OF PRACTICAL PSYCHOLOGISTS' READINESS FOR WORK IN AN INCLUSIVE ENVIRONMENT - Nataliіa Rodina (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article highlights the problem of forming the readiness of practical psychologists to work in an inclusive environment and analyses the latest scientific studies on the outlined problem. It presents the main approaches to the interpretation of the essence of the readiness of practical psychologists for professional activity as well as the components (motivational, cognitive, activity-based), the relevant criteria (awareness and perception, tolerant attitude, active work; general knowledge about the essence of psychological support in an inclusive environment, technological knowledge about diagnosis and monitoring of educational needs of children with problems; diagnostic, preventive, corrective and educational, consultative, educational activities) and the areas of work of specialists with clients in an inclusive environment. The article concentrates on the characteristics of the components of the formation of readiness of practical psychologists for the specified activity. It gives the effective methods and technologies for each component of readiness: psychological and pedagogical observation, emphasis, survey, interviewing, tests and individual tasks). It emphasises the difficulties in the process of conflict situation prevention and the mistakes made when providing correctional and developing services for people with common educational problems. The article determines the prospects for further research, in particular, the introduction of educational disciplines into the educational program that would expand the professional competence of practical psychologists in the process of providing psychological support to clients in an inclusive environment.